'Are we doing Cátedra de Paz?' Teacher perspectives on enacting peace education in Bogotá, Colombia. Issue 3 (2nd September 2022) - Bellino, Michelle J.; Ortiz-Guerrero, Marcela; Paulson, Julia; Ariza Porras, Angie Paola; Cortes, Ibeth Danelly; Ritschard, Sebastian; Sánchez Meertens, Ariel
ABSTRACT: In 2015, the Colombian Ministry of Education introduced the Cátedra de Paz (CdP), a national policy that seeks to contribute to human rights, citizenship, violence prevention, and peaceful conflict resolution. In the context of a decentralized education system, schools have significant autonomy to adapt the policy to local contexts. Relatively little research to date has documented the enactment, evaluation, or impact of the CdP. This study aims to understand how educators have interpreted this national mandate, and the extent to which the policy has prompted and expanded teaching and learning opportunities about conflict, peace, and justice. We explore the perspectives of 46 teachers working in public schools across 19 of Bogotá's 20 localities, several years into the creation of the CdP and in the midst of a contentious national peace process. The paper shows a range of enactment formats and uneven impact on teachers' existing commitments to peace education. We conclude that the CdP has had a contradictory effect on school-based practices, legitimizing the importance of peace education as a national imperative, while marginalizing efforts within schools as individualized and bound to the social sciences subject.